Antioxidant Activity of Facial Gel Moisturizer Formulation From Various Plants: A Literature Review - karunia nining handaningrum; Rini rahmawati; Nina Salamah; adhitya ilham mukti (Universitas Wahid Hasyim Semarang, 2025)
Antioxidants are compounds that can neutralize free radicals, which can damage normal cells, fats, and proteins. Various methods, such as DPPH, ABTS, and FRAP, are used to evaluate the capacity of antioxidant compounds against reactive oxygen species (ROS). Skin ageing, caused by free radicals, pollution, and ultraviolet rays, can be mitigated by using antioxidants, one of which is found in cosmetic preparations such as moisturizers. This study aims to determine the antioxidant activity of various plant extracts in the formulation of a moisturizer gel. The method used is a literature review, with sources from the Google Scholar and PubMed databases, which includes articles from 2014 to 2024, resulting in 9 eligible articles out of 20 screened. The review result showed that plants such as star fruit leaf extract (Averrhoa bilimbi L.) and green tea leaf (Camellia sinensis) have potent antioxidant activity. Starfruit Wuluh (Averrhoa bilimbi L.) extracted with 70% ethanol had an IC50 value of 24.78 ppm, while green tea leaf extract (Camellia sinensis) with 70% ethanol showed an IC50 value of 5.62 ppm in the gel moisturizer preparation. A high IC50 indicates that the compound contains antioxidants that can protect the skin from free radicals, which are formulated into a moisturizing gel. In conclusion, star fruit leaf extract (Averrhoa bilimbi L.) and green tea leaf extract (Camellia sinensis) are highly effective ingredients in moisturiser gel products, as they provide significant antioxidant protection to the ski